AKTIVITAS, KERJASAMA, DAN KOMUNIKASI MUATAN IPAS MENGGUNAKAN MODEL CANGKAL PADA SISWA KELAS IV SDN MURUNG RAYA 3 BANJARMASIN - Rassya Madania Islany; Noorhapizah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research was driven due to the limited degree of engagement., collaboration skills, and communication abilities among fourth-grade students at SDN Murung Raya 3 in IPAS subject. The lack of variety in the learning process made students passive, which negatively affected their learning outcomes. Therefore, CANGKAL model was implemented as a solution to create an active, collaborative, and communicative learning environment. CANGKAL model represents a fusion of three instructional approaches: Inquiry-Driven Education (PBL), Numbered Heads Together (NHT), and Talking Stick. Each model contributes to enhancing key aspects of learning. PBL trains students in problem-solving, NHT promotes participation, and Talking Stick stimulates active communication. This investigation utilized the Action Research approach within a classroom setting, carried out over three phases. The research subjects consisted of 23 fourth-grade students. Research instruments included teacher and student activity observation sheets, observation sheets for collaboration and communication skills, and learning outcome tests. The findings indicated that applying the CANGKAL model proved successful in enhancing learner participation, collaboration, communication, and learning outcomes in the IPAS subject. The implications of this study highlight the importance of collaborative and interactive learning models in creating enjoyable and meaningful learning experiences. Thus, CANGKAL model can serve as an alternative learning strategy at the elementary school level.